2020
DOI: 10.2174/1389201020666191202111534
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Topical Cannabidiol Oil in Symptomatic Relief of Peripheral Neuropathy of the Lower Extremities

Abstract: Background: Peripheral neuropathy can significantly impact the quality of life for those who are affected, as therapies from the current treatment algorithm often fail to deliver adequate symptom relief. There has, however, been an increasing body of evidence for the use of cannabinoids in the treatment of chronic, noncancer pain. The efficacy of a topically delivered cannabidiol (CBD) oil in the management of neuropathic pain was examined in this four-week, randomized and placebocontrolled trial. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(88 citation statements)
references
References 32 publications
0
68
0
3
Order By: Relevance
“…CBD was proven to be safe and cause only mild adverse effects in humans (e.g., ataxia, sedation, nausea, headache or decreased appetite) [100][101][102][103]. A transdermal CBD-containing gel in patients with peripheral neuropathic pain mitigated pain, as well as cold and itchy sensations [104]. CBD might be used clinically alone or in combination with other cannabinoids.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…CBD was proven to be safe and cause only mild adverse effects in humans (e.g., ataxia, sedation, nausea, headache or decreased appetite) [100][101][102][103]. A transdermal CBD-containing gel in patients with peripheral neuropathic pain mitigated pain, as well as cold and itchy sensations [104]. CBD might be used clinically alone or in combination with other cannabinoids.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, these studies were often limited by small cohorts, and the varied disease states indicated that the beneficial effects of CBD are context dependent, which was illustrated in a study where treatment did not improve outcomes in patients suffering from Crohn's disease (Naftali et al, 2014). CBD was also seemingly effective in treatment of chronic pain associated with kidney transplantation and when given topically to patients suffering from peripheral neuropathy of their lower extremities (Cuñetti et al, 2018;Xu et al, 2019). As well, in patients with fibromyalgia, CBD treatment decreased pain by more than 30% in significantly more patients than placebo (Van De Donk et al, 2019).…”
Section: Clinical Outcomes For Cannabidiol In Intractable Chronic Painmentioning
confidence: 99%
“…All images are freely available through pixabay.com under creative commons license. (Ward et al, 2014;King et al, 2017); 3 (Harris et al, 2016); CBD ( 1 NIH; 2 THC Pharm; 3 GW Pharma; 4 Cayman; 5 NS) Rat ↓inflammation; ↓hyperalgesia; ↓ hepatic cytochrome p450 (Costa et al, 2007;Comelli et al, 2008;Casey et al, 2017;Abraham et al, 2019) (Wade et al, 2003) 5 ; (Cuñetti et al, 2018;Xu et al, 2019); (Van De Donk et al, 2019) 2 ; (Notcutt et al, 2004;Capano et al, 2020) 5 ; (Gulbransen et al, 2020) 4 1:1 CBD : THC (GW Pharma. )…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In preclinical studies, it has been shown that cannabidiol (CBD) may directly interact with Nav and Kv channels [143]. In an RCT, testing topical CBD oil in 29 patients with peripheral neuropathic pain compared to placebo, CBD oil showed a more pronounced pain-reducing effect than placebo, but the authors did not discuss the possible Nav blockade as the mechanism of action of CBD applied topically in the painful area [144].…”
Section: Doxepinmentioning
confidence: 99%